Domestic networks contribute to the diversity and composition of live wildlife trafficked in urban markets in Peru - A. Patricia Mendoza; Sam Shanee; Nancy Cavero; Charlene Lujan-Vega; Yohani Ibañez; Cinthya Rynaby; Mirella Villena; Yovana Murillo; Sarah H. Olson; Alberto Perez; Patricia G. Parker; Marcela M. Uhart; et al. (Global Ecology and Conservation, 2022)
Amazonian countries have historically sourced the international wildlife trade. However, little is known about their domestic trade, which is often overlooked in estimates of trafficking. Peruvian law prohibits the unauthorized trade and possession of wildlife, but illegal sales are common in urban markets. To describe the dynamics, diversity, and composition of this illegal trade, we surveyed live wildlife for sale in urban markets in 16 Peruvian departments from 2007 to 2012. We identified the main hotspots of market trafficking, detected 193 species being sold alive, and estimate that 0.35–1.25 million animals were trafficked in this period. Iquitos, Lima, Pucallpa, and Tumbes were the most active and diverse trafficking nodes. Amazonian cities trafficked mostly local species, whereas in other cities the proportion of local species varied significantly (39–67%). Species dissimilarity across cities was high and correlated with their distance along trafficking routes. To assess if the market-based trade was representative of the national trade, we compared species richness in markets with that of country-wide confiscations. At least 430 species were confiscated in Peru between 2001 and 2019, but only 50% of species overlapped with markets in the same cities and period of our surveys. Our data suggest that urban markets are connected in a structured network that provides consumers with a diverse selection of species from across the country. Authorities should consider organizational aspects of trafficking networks to ensure success. Failure to eradicate wildlife trafficking in markets constitutes a serious threat to wildlife conservation and One Health in Peru and beyond.